215k views
24 votes
Please help asap! I don’t understand it

Please help asap! I don’t understand it-example-1
User David Hall
by
4.9k points

2 Answers

5 votes

Explanation:

From given graph

f(-3)= (-3)

f(1)=1

User RJo
by
4.7k points
3 votes

Answer:

f(-3) = -3

f(1) = 1

Explanation:

f(x) means the "function of x".

Therefore, the number in the bracket after the letter f is the value of x.

f(-3) means find the value of the function (y-value) when x = -3

f(1) means find the value of the function (y-value) when x = 1

To find f(-3), find x = -3 on the x-axis.

Now trace vertically until you meet the line. Read the value of y at this point.

⇒ f(-3) = -3

To find f(1), find x = 1 on the x-axis.

Now trace vertically until you meet the line. Read the value of y at this point.

⇒ f(1) = 1

Please help asap! I don’t understand it-example-1
User Chris Trudeau
by
5.3k points